Location Determination of Salatiga City Park Potential with Geographic Information System - Noviarta Rizky Manik; Bistok Hasiholan Simanjuntak (Indonesian Journal of Computing and Modeling, 2018)
Based on Salatiga Urban Land Use Plan 2010-2030, Salatiga still having lacked 30% of the green open space from its area. The addition of the city park is one of the green open space planning that can support the lack, so the research about Salatiga city park location determination with Geographic Information System (GIS) was as one part of the planning of the city park addition. The purpose of the study is ideal location determine for the city park in Salatiga which it was based on population density, population preferences and city park manager, land characteristics, and government regulation about the green open space. The research method was used the descriptive method through quantitative and qualitative approach by utilizing GIS software, questionnaire, and an interview. The research result showed the city park can be developed in protected areas (especially in urban forest sites) or in cultivation areas. However, the city park development must be in accordance with government regulations, land character and land suitability requirements for the city parks. Potential locations for urban parks in Salatiga city can be distinguished by two categories: 1. Recommended class area with 944,584 ha (16.64% of total area) and 2) Highly Recommended class area with 123.37 ha (2.17% of total area).